Patently female from AZT to TV dinners : stories of women inventors and their breakthrough ideas - Vare, Ethlie Ann (Wiley, 2002)
A look at women inventors and their inventions.
Includes bibliographical references and index
Keywords: Octrooien; Uitvinders; Vrouwen; Frau; Women inventors; Women inventors -- United States -- Biography; USA; Biografie